2011
DOI: 10.1111/j.1740-8709.2011.00338.x
|View full text |Cite
|
Sign up to set email alerts
|

Social determinants of iron supplementation among women of reproductive age: a systematic review of qualitative data

Abstract: Iron supplementation for women of reproductive age is a main part of an interdisciplinary strategy recommended for the control and prevention of iron deficiency and the treatment of mild‐to‐moderate iron‐deficiency anaemia. This systematic review reports the findings from a meta‐synthesis of qualitative data concerning the experiences and perceptions of iron supplementation among women of reproductive age and health service providers worldwide. Qualitative systematic review methods were used to conduct a searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
81
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(83 citation statements)
references
References 36 publications
2
81
0
Order By: Relevance
“…7,17,19,25 This is compounded by a lack of recognition of the importance of preventing and treating iron deficiency anaemia, congruence of the symptoms of anaemia with advancing pregnancy and the use of natural or traditional remedies. 17 The aim of this study is to establish an insight into the key themes and trends within a tertiary obstetric hospital that includes a population of high, medium and low risk pregnancies. Themes related to the provision of dietary advice and use of oral iron supplements in pregnancy including; barriers to compliance, types of supplements used, and the timing of commencement and cessation of oral iron supplements were explored.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…7,17,19,25 This is compounded by a lack of recognition of the importance of preventing and treating iron deficiency anaemia, congruence of the symptoms of anaemia with advancing pregnancy and the use of natural or traditional remedies. 17 The aim of this study is to establish an insight into the key themes and trends within a tertiary obstetric hospital that includes a population of high, medium and low risk pregnancies. Themes related to the provision of dietary advice and use of oral iron supplements in pregnancy including; barriers to compliance, types of supplements used, and the timing of commencement and cessation of oral iron supplements were explored.…”
Section: Introductionmentioning
confidence: 97%
“…3,9,10,12,[14][15][16] Gastro-intestinal side effects are frequently cited as a causative factor in reduced compliance to oral iron supplementation in pregnancy. 17,[19][20][21][22][23][24] However studies suggest that education, communication, social and cultural determinants also play a role in lack of motivation to comply with treatment. 7,17,19,25 This is compounded by a lack of recognition of the importance of preventing and treating iron deficiency anaemia, congruence of the symptoms of anaemia with advancing pregnancy and the use of natural or traditional remedies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…An intervention to reduce anemia induced by iron deficiency in pregnant women is distribution of iron supplementation. However, policymakers should consider the context specific determinants and sociocultural influences on the implementation of such programme (Nagata et al, 2012). WHO (2015) showed that India contributes one-third of all global maternal deaths (15 percent).…”
Section: Introductionmentioning
confidence: 99%